Levinas’ ethical perspective: its meaning for education - Rocha de la Torre, Alfredo (Universidad Pedagógica y Tecnológica de Colombia, 2021)
This paper seeks to outline the link between the philosophy of Emmanuel Levinasand education—παιδεία. By taking a distance from attempts to apply the axiologicaland deontological aspects of Levinas’ ethics in education, it is argued that, beyondinstrumentalizing the fundamental categories of the Lithuanian thinker, it is a matter ofunderstanding the meaning of his philosophy and how this can enrich pedagogical practice.The work is carried out in six steps: (1) characterization of Levianasian philosophy as adecentralization of subjectivity and ethical pre-eminence; (2) description of two areasof human experience—enjoyment and Desire—which define (3) two different types ofeducation: for nourishment and for responsibility towards the Other; 4) characterization oftoday’s world as a world of work, of calculation, of skill and of the relation between meansand ends, in which (5) the areas of emergence of a third party—politics, economics, justice,education—are intended to degrade ethics to a second level; and (6) the need to place theface of the Other at the center of the educational act.